Band-Notched UWB Antenna with Switchable and Tunable Performance - Wei Wu; Yun-Bo Li; Rui-Yuan Wu; Chuan-Bo Shi; Tie-Jun Cui (International Journal of Antennas and Propagation)
A band-notched UWB antenna is presented, which can switch between two notch bands and tune the central frequency simultaneously. It is the first time that the switchable and tunable behaviours are combined together in band-notched UWB antennas. In the band-notched structure, PIN diodes are used to switch the lower and upper frequency bands, while varactors could vary the central frequency of each notch band continuously. Measurement results show that the notch bands could switch between 4.2 GHz and 5.8 GHz when the state of varactors is fixed, and the ranges of tuning are 4.2–4.8 GHz and 5.8–6.5 GHz when the state of PIN diodes is ON and OFF, respectively.